The Effect of Information and Communication Technology Disclosure and Corporate Social Responsibility in the Digitalization Process on Company Value - Maulana Fitri Agustin Nur Wahyuni; Saraswati, Erwin; Prastiwi, Arum (Accounting Department, 2024)
Abstract Purpose – This study examines the effect of information and communication technology (ICT) disclosure and corporate social responsibility (CSR) in the digitalization process on company value. Design/Methodology/Approach – This study employed the quantitative content analysis method by collecting and qualitatively analyzing data from the company website followed by quantitative data analysis. The sample of the study was 41 banking companies listed on the Indonesia Stock Exchange during the 2021 period selected using the criteria-based sample selection method. This study used multiple regression analysis. Findings – Research results showed that ICT disclosure on the website in the digitalization process has a positive effect on company value. ICT disclosure on company websites can inform the stakeholders that the management has optimized its resources and implemented innovative business models, improving the efficiency, quality, and consistency of business processes to build a good reputation in the eyes of investors and potential investors. However, CSR disclosure on the company websites has a negative effect on company value due to some issues. Firstly, CSR information disclosed on the company's website is potentially ineffective in increasing operational profitability in the short term. Secondly, banking companies have not properly allocated CSR funds or companies have over-invested in CSR activities. Thirdly, it was found that CSR disclosure during the pandemic had no impact on stock returns. Overall, this study further showed that the disclosure of ICT and CSR complies with the principles of signaling theory because the information serves as a signal concerning the company’s condition to investors which further affects the company’s value. Practical Implications – This research provides a practical contribution for both investors and management. The investors acquire a new source of information in investment decisions making in addition to financial statements, namely such information from non-financial disclosures such as ICT and CSR through easily accessible media. Furthermore, managers gain a new perspective in understanding the potential of ICT and CSR disclosures on websites. Managers need to focus and carefully consider the concept of quality and quantity of information disclosed to the public and stakeholders since abundant information disclosure does not guarantee an increase in company value. Managers need to provide information on ICT and CSR as an approach to meet the needs of stakeholders and influence the decision-making process. Originality/Value – This study uses a banking company as the object of research, where this research is expected to assist the company in making a decision related to understanding potential of ICT and CSR disclosures that can affect firm value. Keywords: ICT disclosure, CSR disclosure, company value Paper Type – Research paper